Estudo da elaboração de uma “cerveja” ale em mosto de alta densidade utilizando mel do semiárido baiano como adjunto do malte - Santana Junior, Jose Francisco Teles de (2019)
With a considerable increase in the demand and development of new biotech products in the food sector and in the case of beer, the presence of products different from those following the conventional trend imposed by the large mass of consumers, Beer was used as an alternative to develop an innovative formulation, with the addition of honey of the Semiarid Bahia, a raw material widely used and commercialized in the food industry and with characteristics of the region mentioned above. The objective of this work was to produce and study, a beer using concentrated wort (high gravity) by the addition of honey from the Semiarid region of Bahia to its formulation. The tests for beer production were made using a statistical planning by means, where it was used concentrations of wort extract in the order of 16, 18, 20, 22 and 24°P.The mosturation was performed by the process of the mosturation ramp being the honey added in the boiling stage. Subsequently, the extract content was corrected to be inoculated with high fermentation yeasts (Ale). Fermentation occurred at temperatures of 15 and 22ºC.The beers were analyzed as: physicochemical characteristics, cell growth and viability, ethanol production, volumetric yield (Qp), substrate conversion in product (Yp/s), the kinetic study of Fermentations and Statistical treatment of the data was performed using the SISVAR 5.0 program.The concentrations (16 and 24°P) were carried out on a pilot scale and performed the sensory analysis, using affective tests and preferably. Through physicochemical analyses it was found that both honey and pure malt wort were able to be used in fermentation.The study of fermentative parameters can be verified that the fermentation conducted at 22ºC presented better results, and that the sample with the highest initial concentration of wort (24°P) had higher volumetric productivity in ethanol (Qp = 0.37g/L.h) and higher Ethanol production (85.90 g/L).With the kinetic study, it is possible to determine the time of yeast generation (Tg= 12.51h), the maximum value of the specific velocity of cell growth (0.05538 h-1) that was obtained under the conditions of lower initial sugar concentration (16°P), velocity specified of apparent extract consumption (0.74125h-1) and specific velocity of product formation (0.37700h-1), was obtained in the sample with the highest initial concentration of wort (24°P).The beer with initial wort of 16°P had 57% of the preference of the takers, while the beer with wort of 24°P had 43%, in relation to the preference test by paired comparison.The audience of sensory analysis manifested their average acceptance in the hedonic scale for the two beers, between "liked very much" and "liked moderately" (averages= 7.5 and 7.25), respectively, with no significant difference between the samples.Thus, this project demonstrated that it is possible to apply this technology, increasing productivity and obtaining economic and energetic benefits, besides valuing a raw material of the Semiarid region of Bahia.